Dielectric metamaterial magnifier creating a virtual color image with far-field subwavelength information - Zhang, Baile (2012)
We propose an approach for far-field optical subwavelength imaging by using a dielectric metamaterial magnifier with gradient refractive index. Different from previous superlens and hyperlens that form a real image with subwavelength features within narrowband, this magnifier creates a virtual color image with sub-100 nm resolution over broadband that can be captured directly by a conventional microscope in the far field. Because the magnifier is made of isotropic dielectric materials, the fabrication will be greatly simplified with existing metamaterial technologies.